PERFUME-INCLUDING COMPLEX PARTICLE AND BATHING AGENT CONTAINING THE SAME - SAEKI TATSUYA (1999)
PROBLEM TO BE SOLVED: To obtain the subject particle capable of instantaneously exhibiting perfume and continuing the perfume in warm water for a long time when using the particle as a bathing agent by integrally compounding a cyclodextrin- inclusion compound of a perfume with an amorphous calcium phosphate. SOLUTION: This complex particle is obtained by integrally compounding (A) a cyclodextrin-inclusion compound of a perfume with (B) an amorphous calcium phosphate on which the perfume is adsorbed. The component A is obtained by stirring an aqueous solution of cyclodextrin and the perfume using a high-speed convection-type stirrer. As the cyclodextrin, β-, or γ-cyclodextrin is preferable. The component B is obtained by mixing the perfume with a surfactant and water to form a dispersion and adding the amorphous calcium phosphate particles to the dispersion and stirring or blending the mixture. The objective particles are obtained by, e.g. adding the component B to a solution containing the component A to be mixed and drying and pelletizing the mixture by a spray drying method.